Method validation of clonidine hydrochloride in human plasma by LC-MS technique - Hossein Danafar (Mazandaran University of Medical Sciences, 2015)
A simple and sensitive high performance liquid chromatography-electrospray ionization mass spectrometry method has been evaluated for the assignment of clonidine hydrochloride in human plasma. The mobile phase composed of acetonitrile–water 60:40 (v/v), and 0.2% formic acid 20 µL of sample was chromatographically analyzed using a repacked ZORBAX-XDB-ODS C18 column (2.1 mm×30 mm, 3.5 micron). Detection of analytes was achieved by tandem mass spectrometry with electrospray ionization (ESI) interface in positive ion mode was operated under the multiple-reaction monitoring mode (m/z 230.0 → 213). Sample pretreatment involved in a one-step protein precipitation (PPT) with methanol and percholoric acid (HClO4) of 0.15 mL plasma. Standard curve was linear (r = 0.998) over the concentration range of 0.01-10.0 ng/ml and showed suitable accuracy and precision. The limit of quantification (LOQ) was 0.01 ng/ml. The method is rapid, simple, very steady and precise for the separation, assignment, evaluation of clonidine healthy in human plasma.